Posterior pituitary neurohormonal disturbances in schizophrenia and role of oxytocin in treatment – need for more short- and long-term studies - Gul O (Dove Medical Press, 2018)
Owais Gul,1 Saqib Gul,2 Abdul Aziz Godil3 1Department of Medicine, Dow Medical College, Dow University of Health Sciences, Karachi, Pakistan; 2Department of Medicine, Hamdard University, Karachi, Pakistan; 3Department of Medicine, Jinnah Medical and Dental College, Karachi, PakistanWe read with great interest the recently published article “Atrial natriuretic peptide and posterior pituitary neurohormone changes in patients with acute schizophrenia” by Guzel et al.1 The study results are vital in understanding the variations among the levels of posterior pituitary neurohormones in patients with acute schizophrenia and seem to be of great value for future therapeutic modifications of the disease.View the original paper by Guzel and colleagues.